For Uncle Charlie: A Conversation With Dr. Kristine Melloy. (September 2020) - Teagarden, Jim; Zabel, Robert; Kaff, Marilyn
Dr. Kristine (Kris) Melloy has enjoyed a varied career ranging from a teacher, special education director, principal, data coach, and professor. Her passion for those who have exceptional needs was formed early and has continued throughout her varied responsibilities. She has received honors and awards for her work and has provided leadership in numerous venues.